Mathematical Reasoning Ability from Student Learning Independence Side in Problem Based Learning Assisted Ethnomathematical Comics Module (Universitas Negeri Semarang, 2022)
This study aims to analyze the ability of mathematical reasoning in terms of learning independence at problem-based learning with the ethnomathematical comic module. The research population was seventh grade students of SMP Ma'arif Kyai Gading. The technique of selecting the sample cluster is random sampling. VIIA as experimental class with problem-based learning with the ethnomathematics comic modules, VIIB as control class with discovery learning. Data collection used documentation, test and non-test. Analysis of quantitative data using completeness test, average difference test, regression test. Qualitative data analysis using validity test, data reduction, data presentation, conclusion drawing. The results of the study of students with high learning independence achieved indicators of mathematical reasoning ability with few errors, so that they were declared good, students with low learning independence only achieved several indicators of mathematical reasoning ability, so that they were declared less good.